PESANTREN DAN PENGEMBANGAN KURIKULUM KEWIRAUSAHAAN: Kajian Pesantren Roudahtul Khuffadz Sorong Papua Barat - Suardi Wekke, Ismail (INFERENSI, 2012)
AbstractPesantren is a unique instrument of Indonesian educational system.Environmental adaptations enhance pesantren to modify institutionalchange and development. Therefore, this research will explore howpesantren widen the curriculum in term of enterprenurship. This studywas conducted in pesantren Roudhotul Khuffadz. It is located in Sorong,West Papua province, eastern part of Indonesia. In depth-interview andnon participant observation were attended in collecting data. In term ofefforts to identify data validity, the research was extended from threemonths to six months. The study shows that the pesantren RoudhotulKhuffadz was presented many examinations and discussion in developingits curriculum. In addition, they decided to empower curriculum withentrepreneurship aspects. This decision was concluded to extend localneeds and students skills in enlarging their opportunities after schoolage. Finally, this study recommends identifying socio-cultural inpesantren environment in order to understand curriculum improvement.Â Â